Applcation of Red Dragon Fruit Extract (Hylocereus polyrhizus) as an Antioxidant in Lip Cream Preparation - Suharyani, Ine; Rindiyani, Rindiyani; Senja, Rima Yulia; Falya, Yuniarti; Nurdianti, Lusy (Indonesian Journal of Pharmaceutics, 2023)
Later, women cannot separated from cosmetics, such as lip cream. However, many lip creams contains synthetic dye that sometime harmful for our body. Therefore red dragon fruit (Hylocereus polyrhizus) can  used as natural dyes in a  lip cream preparation. In addition, red dragon fruit contains anthocyanins, a group of flavonoid, that has efficacy as an antioxidants. This study aim to develope lip cream as cosmetic preparation containing of red dragon fruit for antioxidant. The extraction was done by Microwave Assisted Extraction (MAE) using ethanol 95%:aquadest (4:1).  Lip cream preparations were made in 3 formulas with varying concentrations of extract, 5% (LCE5), 10% (LCE10) and 15% (LCE 15). The extraction uasing MAE method was yielded the rendemen of 44,12%. Evaluation of the preparations carried out included organoleptic, pH, homogeneity, and spreadability, while antioxidant activity were carried out using spectrophotometry UV-Vis with the DPPH (2,2-diphenyl-1-picrylhidrazyl) method. The results showed that all lip cream formulas fulfill the requirement i.e organoleptic, pH, homogeneity, and spreadability. The antioxidant activity of LCE5, LCE10 and LCE15 were 195.26 ± 0.40, 174.94 ± 0,63, and 168.27 ± 0.60, respectively. All the preparation has medium antioxidant activity but LCE15 has a stronger antioxidant activity due to the smallest IC50 compared to LCE5 and LCE10. This result underlying the application of red dragon fruit extract as an antioxidant agent in lip cream preparation.